FACTORS AFFECTING MATERNAL COMPLIANCE IN GIVING MULTIPLE IMMUNIZATION INJECTIONS TO TODDLERS AT MEDOKAN AYU HEALTH CENTER IN SURABAYA - Samson, Kristoforus; Husada, Dominicus; Muthmainnah, Muthmainnah (Universitas Airlangga, 2025)
Maternal compliance as determining factor in increasing the coverage of double immunization injections for children <2-years-old at the Medokan Ayu Health Center in Surabaya. Based on local monitoring data, the average immunized child is still below the target of 90% which is certainly at high risk of exposure to hepatitis-B, tuberculosis, whooping cough, and diphtheria in children. This study aimed to analyze the factors that affect maternal compliance in administering double immunization injections to children <2-years-old at the Medokan Ayu Surabaya Health Center. This was observational research with a cross-sectional study design. Data was collected using questionnaires distributed directly to respondents. The population in this study was mothers who have children <2-years-old at the Medokan Ayu Health Center in Surabaya. Sample selected using the Multistage Random Sampling technique. There was no influence between demographic factors on maternal compliance in administering double immunization injections to children <2-years-old at the Medokan Ayu Health Center in Surabaya (p=0.855). There were effects of perceived vulnerability, perceived severity, perceived benefits, perceived obstacles, belief in success (self-efficacy), and signals to action on maternal compliance in administering double immunization injections to children <2-years-old at the Medokan Ayu Surabaya Health Center (p< 0.05). Mothers who have perceived obstacles, as well as disbelief in the success of double immunization injections tend to disobey in providing immunization injections to their children. The latest program from the Health Center which is home immunization visits is a to increase the coverage of double immunization injections for children <2-years-old.